PENGARUH KEBIJAKAN RESTRUKTURISASI PEMBIAYAAN, UKURAN BANK, NON PERFORMING FINANCING, DAN PRODUK DOMESTIK BRUTO TERHADAP STABILITAS PERBANKAN SYARIAH DI INDONESIA: BUKTI EMPIRIS DI TENGAH PANDEMI COVID 19 - Ahmad Fatoni (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
Abstract: This study aims to analyze the effect of financing restructuring policies through regulation No. 11/ POJK.03/2020 on the stability of Islamic banking in Indonesia. This study uses panel data from the 6 largest Islamic banks in Indonesia for the period September 2018 to December 2020. This study uses the Random Effect Model as the best estimation model. The results showed that the financing restructuring policy had a negative and significant effect on the stability of Islamic banks. Meanwhile, Non-Performing Financing (NPF) and Gross Domestic Product (GDP) as control variables have a significant positive effect on the stability of Islamic banks. Meanwhile, inflation has a negative and significant effect on the stability of Islamic banks. This study did not find the effect of bank size on the stability of Islamic banking in Indonesia. Keywords: Islamic Banking Stability, Financing Restructuring